Pengaruh Corporate Social Responsibility Terhadap Agresivitas Pajak Dengan Kualitas Audit Sebagai Variabel Moderasi - Bella Refiana Wulandari; Maria Goreti Kentris Indarti; Jacobus Widiatmoko (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The main objective of this research is to analyze the impact of business responsibility and audit quality on tax aggressiveness. This research also investigates the role of audit quality as a moderating variable in the relationship between corporate social responsibility and tax aggressiveness. This research uses information from manufacturing industries listed on the IDX for the 2020-2022 period. Based on purposive sampling procedures, information was obtained on 153 companies. Hypothesis testing was analyzed using moderated regression analysis (MRA). The analysis obtained shows that corporate social responsibility has a negative influence on tax aggressiveness. However, audit quality does not affect tax aggressiveness and the audit quality variable cannot moderate the negative relationship of business responsibility to tax aggressiveness. Roa and size as control variables also do not affect tax aggressiveness. Keywords: Tax Aggressiveness, Corporate Social Responsibility, Audit Quality, Profitability, Company Size